(untitled) (Philologia, 2021)
This paper analyses some basic literary techniques in Paradise Lost which serve to fill in the narrative text of the epic with the poritons of text that do not exist in the original Biblical story, those being: the non-human initiators of the action, a variety of temporal axes and the retardations of the narrative tempo.